Transformational Leadership At Madrasah Tsanawiyah Ma'had Al-Zaytun - Sulthon Mujahidin; Asifa Hijrotul Madinah; Siti Khumayah; Aghnia Dian Lestari (Annpublisher, 2025)
Background. This research is based on the problem of teacher and student discipline at Madrasah Tsanawiyah Ma'had Al-Zaytun, which, despite having strict rules and a clear vision, still shows low participation and awareness of intrinsic discipline. Aims. This research aims to examine how school principals apply the four dimensions of Transformational leadership: influence, idealized-inspirational motivation, intellectual stimulation, and individual consideration. Methods. In fostering a culture of discipline and increasing school residents' involvement, using descriptive qualitative methods such as observation, in-depth interviews, and documentation. This study analyzes the leadership practices of school principals in the natural context of madrasas. Result. The results of the study show that examples of leadership, visionary communication, support for learning innovation, a humanistic approach, and an educational and restorative disciplinary system can create an orderly, supportive, and motivating learning environment. Transformational leadership has been shown to work in an integrated way to foster discipline as an internal value, not just formal compliance. Conclusion. The conclusion of the research is that transformational leadership is an effective strategy to strengthen the culture of educational organizations. Implementation. It is recommended that schools continue to develop affirming two-way communication, continuous character development, and pedagogical innovation to maintain the quality of discipline and motivation to learn.